2008
DOI: 10.1166/jnn.2008.sw16
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Hansen Solubility Parameters Theory to Carbon Nanotubes

Abstract: Carbon nanotubes (CNT) are very promising nano-objects due to their exceptional properties. However, their tendency to form bundles as well as their insolubility in common solvents makes them difficult to handle. The main way to solve the problem is chemical or physical CNTs functionalisations, with all the problems inherent to the methods. In this contribution, we present a new approach that allows predicting the solubility of carbon nanotubes in many solvents but also predicting the most appropriate solvents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
80
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 0 publications
11
80
1
Order By: Relevance
“…This gave a clear peak for solvents with δ T~2 3 MPa 1/2 . This suggests that nanotubes can be treated as a molecule with Hildebrand parameter close to 23 MPa 1/2 , in line with measurements by Detriche et al [20] and Ham et al [56] . However, the peak was not very well defined as many solvents with δ T close to the peak displayed lower than expected nanotube concentrations.…”
Section: Solubility Parameterssupporting
confidence: 90%
See 2 more Smart Citations
“…This gave a clear peak for solvents with δ T~2 3 MPa 1/2 . This suggests that nanotubes can be treated as a molecule with Hildebrand parameter close to 23 MPa 1/2 , in line with measurements by Detriche et al [20] and Ham et al [56] . However, the peak was not very well defined as many solvents with δ T close to the peak displayed lower than expected nanotube concentrations.…”
Section: Solubility Parameterssupporting
confidence: 90%
“…In addition Maeda et al [23] showed that SWNT could be dispersed in mixtures of tetrahydrafuran with various amines. More recently, Detriche et al [20] and…”
Section: Dispersion and Exfoliation Of Nanotubes In Solventsmentioning
confidence: 95%
See 1 more Smart Citation
“…Analysis based on Hansen solubility parameter has been applied to dispersed nanomaterials such as carbon nanotubes 33,61,62 and graphene 25,63 in recent years.…”
Section: S D Ns P S P Ns H S H Ns S Vvmentioning
confidence: 99%
“…Thus, the very nature of the SWNTs and their solubility, is also dependent on the sonication time and the identification of a characteristic and unique set of solubility parameters is difficult. In the study of Bergin et al [13], each sample was sonicated for 30mins with ice cooling, whereas in the work of Detriche et al [16,18] . There is thus considerable discrepancy between the studies already reported in literature and it is notable that the types of nanotubes and the preparation conditions very significantly between studies.…”
Section: Methodsmentioning
confidence: 99%